Large global volatility shocks, equity markets and globalisation: 1885-2011 - Arnaud Mehl (European Central Bank (ECB), 2013)
I estimate the transmission of large global volatility shocks in international equity markets from the earlier (pre-1914) to the modern era of globalisation. To that end, I identify 43 such shocks over the period 1885-2011, defined as significant increases in unanticipated volatility in US equity markets, which I relate to well-known historical events. My estimates suggest that the response of global equity markets to these shocks in a panel of 16 countries is both statistically significant and large economically. On average, global equity market valuations correct by about 20% in the month when a shock occurs. There is substantial heterogeneity in responses both across countries and time, however, which can be partly explained by differences in global trade integration. I find no evidence that other potential theoretical determinants, such as output composition, country fundamentals or global policy responses matter, by contrast. These results shed light on a neglected aspect of globalisation, which creates opportunities but also heightens the exposure of economies to acute surges in global uncertainty and risk aversion.
Keywords: F30; F31; N20; 330; equity markets; Globalisation; international linkages; large global volatility shocks